Pelaksanaan hibah harta bercagar dalam industri perancangan dan pengurusan harta orang Islam - Noor Lizza Mohamed Said; Wan Amirul Adli Wan Ayub (Penerbit Universiti Kebangsaan Malaysia, 2021)
The credit convenience through loan installment made it easier for the society to own an unmovable property. However, the emerging issue of the matter is it also contributes to loads of frozen assets. The concept of hibah is being applied as introductory step in planning assets so it can continuously be benefitted. However, the policy practiced by the banks is still not allowing any charged property to be transferred through hibah besides the property as it also does not fully belong to the buyer. This research analyzes the implementation of hibah for charged property according to fuqaha’s view and observe the product implementation in Malaysia Law. This research is conducted by qualitative method using document analysis as the design of the research. The findings indicated that hibah of charged property is valid according to some of the fuqaha’s view with a few conditions. The differences in the verdicts of courts in Syariah Courts about the hibah cases however confirmed that hibah is being accepted in institutions. Few challenges and weaknesses have to be overcome to implement the product so that it can not be challenged by any party. The solution between hibah document provider and the loan provider has to be quickly executed in order for a guaranteed implementation of the product.